2001
DOI: 10.1093/jnci/93.16.1204
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Treatment of Anemia Associated With Cancer Therapy: a Systematic Review and Meta-analysis of Controlled Clinical Trials

Abstract: Epoetin treatment offers an attractive but costly alternative to red blood cell transfusion for managing anemia associated with cancer therapy. The goal of this review is to facilitate more efficient use of epoetin by 1) quantifying the effects of epoetin on the likelihood of transfusion and on quality of life in patients with cancer treatment-related anemia and 2) evaluating whether outcomes are superior when epoetin treatment is initiated at higher hemoglobin thresholds. Two independent reviewers followed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(112 citation statements)
references
References 43 publications
4
101
0
7
Order By: Relevance
“…Phase I/II and randomized trials have demonstrated the beneficial effects of this option in improving Hb levels in patients with malignant disease, with rapid and pronounced responses having been observed. 29 The use of erythropoietin in patients receiving radiotherapy or chemoradiotherapy has been examined only recently, 30 -34 and it remains uncertain whether such an approach will improve treatment outcome. In fact, a recent randomized trial reported poorer locoregional control in patients randomized to receive erythropoietin during radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I/II and randomized trials have demonstrated the beneficial effects of this option in improving Hb levels in patients with malignant disease, with rapid and pronounced responses having been observed. 29 The use of erythropoietin in patients receiving radiotherapy or chemoradiotherapy has been examined only recently, 30 -34 and it remains uncertain whether such an approach will improve treatment outcome. In fact, a recent randomized trial reported poorer locoregional control in patients randomized to receive erythropoietin during radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Both epoetin alfa and epoetin beta have been shown to be effective in correcting Hb levels and to reduce the need for RBC transfusions compared with placebo in several randomized clinical trials. 13 The recommended dose frequency for epoetin alfa and epoetin beta was three times per week (TIW).…”
Section: Early 1990s To Mid-2000s: Developmentmentioning
confidence: 99%
“…7 To determine whether these early observations were substantiated by subsequent studies, and to evaluate whether there now exists a substantial body of evidence in favor of early intervention, we included these studies in our analysis, in addition to the five studies we identified using our search criteria. 10,20,24,27,30 Transfusion outcome Table 2 summarizes the transfusion outcomes of all seven studies.…”
Section: Are There Clinical Benefits Associated With Initiating Erythmentioning
confidence: 99%
“…5 Clinical practice guidelines for the management of CIA, issued jointly by the American Society of Clinical Oncology (ASCO) and the American Society of Hematology (ASH), 6 have recommended the use of erythropoietic agents in patients with hemoglobin Յ 10 g/dL. These recommendations were based on a systematic review of the literature (from 1985 to 1999) on the effectiveness of erythropoietic proteins for the treatment of CIA that included 22 randomized controlled trials (RCTs) in 1927 patients 7 (Table 1). In contrast, the guidelines made no definitive recommendation for patients with Grade 1 anemia.…”
mentioning
confidence: 99%